Digitalization Reform Of Land Certification In The Batam Free Trade Zone And Free Port Area - Siti Nurkhotijah; Soerya Respationo; Khairul Riza (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the urgency, challenges, and prospects of law enforcement in the implementation of land certificate digitalization in the Batam Free Trade Zone and Free Port Area (KPBPB Batam). The digitalization of land certificates, particularly through the application of electronic certificates, is expected to strengthen legal certainty, prevent document forgery, expedite administrative processes, and enhance transparency in land governance in Indonesia. However, the dual authority of the Batam Authority (BP Batam) and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) creates regulatory and institutional complexities that have the potential to trigger conflicts in land management. The research method used is normative-empirical with a statute approach, case approach, and socio-legal analysis, supported by primary data in the form of interviews with BP Batam officials, ATR/BPN, notaries/PPAT, and secondary data comprising laws and regulations, legal literature, and related decisions. The results of the study indicate that although the digitalization of land certification offers significant potential to support investment and sustainable development in Batam, its implementation is still hampered by overlapping regulations, weak institutional coordination, limitations of technological infrastructure, and the unpreparedness of human resources. This study concludes that legal reform and regulatory harmonization between BP Batam and ATR/BPN are the main prerequisites for the successful digitalization of land certificates. In addition, strengthening law enforcement mechanisms, implementing the principles of good governance, and ensuring transparent oversight are key to preventing the abuse of authority and land disputes. The contribution of this research lies in enriching the discourse on land law reform in special economic zones and providing policy recommendations for the government, legal practitioners, and investors in facing the challenges of implementation.